Effect of dietary resveratrol supplementation on growth performance, antioxidant capacity, intestinal immunity and gut microbiota in yellow-feathered broilers challenged with lipopolysaccharide - He, Zhentao; Li, Yaojie; Xiong, Taidi; Nie, Xiaoyan; Zhang, Huihua; Zhu, Cui (Frontiers in Microbiology, 2022)
This study was carried out to investigate the effects of dietary resveratrol (RES) supplementation on growth performance, antioxidant capacity, intestinal immunity and gut microbiota in yellow-feathered broilers challenged by lipopolysaccharide (LPS). A total of 240 yellow-feathered broilers were randomly assigned to four treatment groups in a 2 × 2 factorial design. The broilers were fed with the control diet or control diet supplemented with 400 mg/kg RES, followed by challenge with LPS or the same amount of saline. Dietary RES supplementation significantly alleviated the decreases in the body weight (BW), average daily gain (ADG), and ADFI induced by LPS (P < 0.05). LPS challenge significantly increased plasma concentrations of triglyceride, high-density lipoprotein cholesterol (HDL-C), aspartate aminotransferase (AST), and cortisol levels. but decreased triiodothyronine (T3) and insulin levels (P < 0.05). Dietary supplementation with RES significantly reversed the elevated creatinine concentrations and the decreased concentrations of T3 and insulin caused by LPS (P < 0.05). Moreover, dietary RES supplementation significantly increased plasma total antioxidant capacity (T-AOC) and catalase (CAT) activities and gluperoxide dismutase (SOD) and T-AOC activities in jejunal mucosa and reduced malondialdehyde (MDA) concentration in the plasma (P < 0.05). The reduction in the villus height to crypt depth ratio (VH:CD) in duodenum, jejunum and ileum and the shortening of villi height in jejunum and ileum caused by LPS were also alleviated by RES treatment (P < 0.05). Furthermore, the increased concentrations of intestinal necrosis factor-α (TNF-α), interleukin-6 (IL-6), and IL-1β caused by LPS were significantly decreased by RES treatment (P < 0.05). Dietary RES treatment increased the mRNA expression of claudin-1, claudin-5, occludin and zonula occludens-1 (ZO-1), and decreased mRNA expression of IL-1β, IL-8, IL-17, and TNF-α after LPS challenge (P < 0.05). Dietary RES treatments significantly decreased the dominance of cecal microbiota, and increased the Pieiou-e and Simpson index Moreover, dietary RES supplementation increased relative abundance of UCG_ 009, Erysipeiotrichaceae, Christensenellaceae_R-7_group, Anaerotruncus, RF39, and Ruminococcus while decreasing the abundance of Alistipes at genus level. Collectively, dietary supplementation with 400 mg/kg RES could improve growth performance and antioxidant capacity, and modulate intestinal immunity and gut microbiota in yellow-feathered broilers.